Pengaruh Penggunaan Antikolinergik Terhadap Gangguan Fungsi Kognitif Pada Pasien Geriatri di Lombok Tengah, Indonesia - Lupitaningrum, Dita Marina; Rahmawati, Fita (Pharmaceutical Sciences and Research, 2019)
Geriatrics are more susceptible to the unwanted effects of drugs, such as potential cognitive impairment effects of anticholinergic drugs. This study aims to determine the effect of anticholinergic drug use on cognitive reduction in Central Lombok geriatric patients. This cross-sectional study was conducted by tracing a medical history and interview result using a Six-item Cognitive Impairment Tests (6-CIT) questionnaire to measure cognitive function. The sample size was 503 geriatric patients with 213 patients as users and 290 patients as non-users. Anticholinergic loads were determined in each patient using Anticholinergic Drug Scale (ADS). The data of the study were analyzed using Chi-square to see the effect of anticholinergic drug use on cognitive function reduction. A total of 168 patients (78.9%) used a single anticholinergic drug. Most of anticholinergic used were level 1 (95.8%). Patients who had a total anticholinergic load of 1 were 156 people (73.2%). In the user group, 191 patients (38%) experienced cognitive reduction. The most common disease experienced by drug user was circulatory system disease (50.9%) and the most widely used drug was furosemide (45.4%). Chi-square analysis showed that anticholinergic drug had significant effect on geriatrics impairment of cognitive function (OR 2.361; CI95% 1.399-3.983; P=0.002). The use of anticholinergic drugs had an effect on cognitive reduction in geriatric patient.